Pola Komunikasi Dan Proses Akulturasi Mahasiswa Asing Di STAIN Kediri - Siti Amanah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
The research aims to: (1). describe the patterns of communication employed by Thai students to facilitate theÂ process of their adaptation and acculturation with the Indonesian culture especially in the environment STAINÂ Kediri ; (2). to identify and describe internal and external factors that facilitate Thai students in the process ofÂ adaptation and acculturation with culture, especially in the Kediri .Â This study is categoried into descriptive research type with qualitative method. Methods of collecting data areÂ by using direct observation, participative, in depth interview and documentation. The respondents were takenÂ with purposive sampling technique. The data analysis applied is Miles and Hubermanâ€™s interactive model ofÂ data analysis which consist of data reduction, data display, conclusion drawing and verification.Â The result shows that: (1) the communication patterns that are applied to facilitate the process of adaptation andÂ acculturation with the culture of Indonesia in the environment STAIN Kediri are interpersonal communicationÂ with friends countrymen, friends in campus, and nearby residents. There was also a group communication toÂ perform routine discussion and groups of discussion; (2) Internal factors that help the process of adaptationÂ and acculturation is a psychological adaptation that is the motivation of their friends and countrymen, whileÂ external factors are socio-cultural adaptation that is intended to improve interaction with the new culture,Â their land lady and their friends. In addition, the potential of acculturation include similarities in terms ofÂ religion, race, environment, similar language (i.e. Malay), educational background, open personality, knowledgeÂ about Indonesia. Besides, the age of Thai students who are still young make them easy to be accustomed withÂ new culture and environment.